# A simple question on Multinomial Distribution?

The probability of choosing $(n_1, \space n_2, \space \cdots \space n_k)$ randomly from a set of $(N_1, \space N_2, \space \cdots \space N_k)$ such that for $1\le i\le k, \space i\in \mathbb N$

• $n_i \le N_i$
• $\displaystyle \sum_{1\le i\le k} n_i = n$
• $\displaystyle \sum_{1\le i\le k} N_i = N$
• $p_i = \cfrac {N_i}{n_i}$

is $$\cfrac {n!} {n_1!\cdots n_k!}p_1^{n_1}\cdots p_k^{n_k}$$ The number of possible outcome is $N^n$ while the number of required outcome is $\cfrac {n!} {n_1!\cdots n_k!} N_1^{n_1}\cdots N_k^{n_k}$.

My question breaks down to proving that $$\displaystyle \prod_{1\le i\le k} \left(\! \begin{array}{c} n - (n_1 + n_2 + \cdots +n_{i-1}) \\ n_i \end{array} \!\right) = \cfrac {n!} {n_1!\cdots n_k!}$$

-

Note that you have $\binom nk = \frac{n!}{k!(n-k)!}$ and hence \begin{align*} \prod_{i=1}^k \binom{n - (n_1 + \cdots + n_{i-1})}{n_i} &= \prod_{i=1}^k \frac{\bigl(n - (n_1 + \cdots + n_{i-1})\bigr)!}{n_i!\cdot \bigl(n - (n_1 + \cdots + n_{i-1} + n_i)\bigr)!}\\ &= \prod_{i=1}^k \frac 1{n_i!} \prod_{i=1}^k \frac{\bigl(n - (n_1 + \cdots + n_{i-1})\bigr)!}{\bigl(n - (n_1 + \cdots + n_{i-1} + n_i)\bigr)!}\\ &= \prod_{i=1}^k \frac 1{n_i!} \cdot \frac{n!}{\bigl(n-(n_1 + \cdots + n_k)\bigr)!}\\ &= \frac{n!}{n_1! \cdots n_k!} \end{align*} so its just your term in another form.
why do you have double product there and how did $n!$ appear? – user31280 Oct 25 '12 at 11:27
$n!$ is the numerator of the first product for $i = 1$ (then there is no $n_j$ to be subtracted) and the "double" product arises from $\prod_i a_i b_i = \prod_i a_i \cdot \prod_i b_i$ – martini Oct 25 '12 at 11:45